2012
DOI: 10.1096/fj.11-191932
|View full text |Cite
|
Sign up to set email alerts
|

AT1receptor blockade delays postlactational mammary gland involution: a novel role for the renin angiotensin system

Abstract: Angiotensin II (AngII), the main effector peptide of the renin-angiotensin system (RAS), participates in multiple biological processes, including cell growth, apoptosis, and tissue remodeling. Since AngII activates, in different cell types, signal transducing pathways that are critical for mammary gland postlactational regression, we investigated the role of the RAS during this process. We found that exogenous administration of AngII in mammary glands of lactating Balb/c mice induced epithelium apoptosis [2.9±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Apoptosis is reportedly common in atrophy of exocrine glands. For example, epithelial cell numbers decrease by apoptosis during involution of the lactating mammary glands after weaning [29]. Acinar cells undergo apoptosis in the atrophic pancreas induced by duct obstruction [40], and similar observations were reported in atrophy of parotid glands following duct ligation [11,27].…”
Section: Introductionsupporting
confidence: 63%
“…Apoptosis is reportedly common in atrophy of exocrine glands. For example, epithelial cell numbers decrease by apoptosis during involution of the lactating mammary glands after weaning [29]. Acinar cells undergo apoptosis in the atrophic pancreas induced by duct obstruction [40], and similar observations were reported in atrophy of parotid glands following duct ligation [11,27].…”
Section: Introductionsupporting
confidence: 63%
“…The importance of AT 1 R function on mammary gland morphogenesis during normal development and pregnancy has been characterised by Nahmod and colleagues using mice deficient in either, or both, of the two different murine angiotensin receptors (AT 1A or AT 1B ) and with the administration of Irbesartan, an ARB [40]. Of the two angiotensin receptors, AT 1A, the ortholog of human AT 1 R, mediated signaling was important in tissue remodeling during postlactational mammary gland involution.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported by the cited authors together with our present study show how the RAS can play different roles depending on the stage of mammary gland development and differentiation. 33 Puddefoot et al demonstrated that treatment of MCF-7 cells with AngII for 48 h caused concentration-dependent reduction in adhesion to fibronectin, laminin and collagen type IV-coated inserts. This significant inhibition of MCF-7 cell adhesion to fibronectin, laminin and collagen type IV by AngII was attenuated by incubation with the AT1-R antagonist losartan.…”
Section: Discussionmentioning
confidence: 99%